METHOD OF TRANSFERRING WORD MEANING (Multidisciplinary Journal of Science and Technology, 2023)
The words represent the concept of them not self-like, action, character in existence, such as the act, the character. The concept is a generalized reflection of what is objective in the minds in the minds of the person. The concept of something that combines the general signs of this type of things. Apparently, there is general between lexical sense and the concept. Words also have a unique semantic structure, such as having a unique phonetic, a word with a morphological structure. The lexical meaning that includes the semantic structure of the word is also made up of certain components. This is what the same thing is reflected in this article